PENERAPAN ADMINISTRASI PERKANTORAN BERBASIS DIGITAL PADA PEMERINTAH DAERAH KOTA BANDUNG (STUDI DESKRIPTIF DI DINAS KOMUNIKASI DAN INFORMATIKA KOTA BANDUNG) - Alya; Intan Rahmawati; Benorio Denatan; Erni; Nur Azizah; Elyana Hutahaen (Jurnal Administrasi Perkantoran dan Kesekretariatan, 2026)
The implementation of digital-based office administration is part of bureaucratic transformation to improve government effectiveness and efficiency. This study aims to examine the implementation of digital-based office administration in the Bandung City Regional Government, specifically the Communication and Informatics Office, and to identify the benefits and challenges of its implementation. The research method used is descriptive qualitative through a literature review utilizing secondary data in the form of scientific journals and policy documents. The results of the study indicate that digitalization of office administration can accelerate work processes, improve coordination between units, and support government transparency and accountability. However, its implementation still faces obstacles related to human resource competency, infrastructure readiness, and resistance to change. Keywords: Digital Office Administration; Digitalization; E-Government; Regional Government; Communication and Informatics Office.